2014
DOI: 10.1128/jvi.01533-14
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Human Papillomavirus E6 Protein Promotes Reprogramming of Fanconi Anemia Patient Cells through Repression of p53 but Does Not Allow for Sustained Growth of Induced Pluripotent Stem Cells

Abstract: DNA repair plays a crucial role in embryonic and somatic stem cell biology and cell reprogramming. The Fanconi anemia (FA) pathway, which promotes error-free repair of DNA double-strand breaks, is required for somatic cell reprogramming to induced pluripotent stem cells (iPSC). Thus, cells from Fanconi anemia patients, which lack this critical pathway, fail to be reprogrammed to iPSC under standard conditions unless the defective FA gene is complemented. In this study, we utilized the oncogenes of high-risk hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…In addition, studies have demonstrated an interaction between the HPV16 E7 oncoprotein and the FA pathway. [38][39][40] It has also been hypothesized that the FA pathway contributes to the repair of DNA damage induced by HPV16 E7, providing one explanation for why FA patients are predisposed to HPV-associated HNSCCs. 41 In FA patients from North America, a high percentage (84%) of HNSCCs were found to be positive for highrisk HPV DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have demonstrated an interaction between the HPV16 E7 oncoprotein and the FA pathway. [38][39][40] It has also been hypothesized that the FA pathway contributes to the repair of DNA damage induced by HPV16 E7, providing one explanation for why FA patients are predisposed to HPV-associated HNSCCs. 41 In FA patients from North America, a high percentage (84%) of HNSCCs were found to be positive for highrisk HPV DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of pathological stress, including radiation, 137,138 hypoxia, 139 and oncogene expression, 140 checkpoints that restrict developmental cellular outputs can be lifted, allowing cells to reprogramme for 'stemness' . 141 Such reprogramming could be an essential part of normal healing, but during fractionated courses of radiation it could generate a nidus for recurrence.…”
Section: Cancer Stem Cells and Radiotherapymentioning
confidence: 99%
“…Reprogramming induces the DDR [99] and activates the FA pathway [94], leading to P53-mediated apoptosis and low reprogramming efficiency [96]. This is partially circumvented by preventing reactive oxygen species (ROS)-mediated DNA damage [94] or by suppressing P53 during reprogramming using RNA interference [96] or human papillomavirus P53-repressing E6 protein [100]. Safe and controlled FANCA gene correction was achieved using integration-free genome editing by genetic recombination with helper-dependent adenoviral vectors [96] or by targeting FANCA insertion into the safe locus AAVS1 [97] using engineered nucleases ("safe harbor" strategy) [101].…”
Section: Novel Therapies: From Genes To Patientsmentioning
confidence: 99%